Investigation of cytokine gene polymorphisms in patients with psoriasis vulgaris - Cinar, Cigdem Kekik; Karahan, Gonca Emel; Temurhan, Sonay; Pirmit, Serpil; ONSUN, Nahide; ONSUN, NAHIDE; Oguz, Fatma Savran (My University, 2016)
Psoriasis is associated with cutaneous and systemic overexpression of several proinflammatory cytokines. The aim of this study was to investigate the relationship between susceptibility to psoriasis and polymorphisms of tumor necrosis factor alpha (TNF-alpha), interferon gamma (INF-gamma), interleukin (IL-10), IL-6 and transforming growth factor beta (TGF-beta). Eighty-nine patients with psoriasis and 201 healthy controls were enrolled into the study. The patient group was divided into 2 subgroups as early-onset (group 1) and late-onset (group 2). The cytokine gene polymorphisms in each group were determined by polymerase chain reaction-single specific primer. When the whole and only group 1 patients were compared with the controls, TGF-beta TT/GC genotype was significantly high in the whole and group 1 patients. When we compared the group 1 and group 2, the frequency of IFN-gamma AA genotype was found to be significantly high in group 1 which lost significance after Bonferroni correction. Patients with moderate symptoms had a significantly high frequency of IL-10 GCC/GCC genotype that did not remain significant after correction. These data from our small group of patients demonstrated that the only significant difference between the whole patient group and the controls was for TGF-beta TT/GC genotype with a higher frequency in the patients. Due to the involvement of many other genes relating to the activity of Th1 cytokines, further studies are required to determine the molecular basis of the susceptibility to psoriasis.